Foreign direct investment, democracy, and development : assessing contours, correlates, and concomitants of globalization - De Soysa, Indra (London ; New York : Routledge, 2003)
Using quantitative data, this book addresses internationalisation by focusing on the impact of Foreign Direct Investment and democracy on economic development and the effects of economic internationalisation on democracy.
Includes bibliographical references (p. [133]-148) and index.
aia 18/7/16
Loan
Keywords: International economic integration; Investments, Foreign; International trade; Investments, Foreign; Globalization; Democracy; Developing countries